Studi Analisis Fenomena January Effect Saham Bank Umum Pemerintah Periode 2016-2019 - Prihatiningsih Prihatiningsih; Mohammad Rois (The Indonesia Capital Market Institute, 2021)
This study aimed to analyze whether there are seasonal anomalies (January Effect) on Stock Company Banking is included in LQ-45 and listed in Indonesia Stock Exchange Period of 2016 - 2019, by seeing of differences in stock returns and trading volume activity in January with other months. The population of this study are Stock of Companies is included in the LQ-45 listed in the Indonesia Stock Exchange, which 3 companies have been selected as the sample using purposive sampling techniques. Data analysist techniques are performed by One Way ANOVA and Non Parametric Kruskall Wallis test. The result of analysist showed that there were significant differences in stock return in January with other months, and there were significant differences too in trading volume activity in January with other months, but the stock return and trading volume activity in January isn’t the highest among other months, so that the January Effect was not shown to occur in the Banking Companies is included in the LQ-45 and listed in Indonesia Stock Exchange Periods of 2016-2019